Equilibrium exchange rates in the transition: the tradable price-based real appreciation and estimation uncertainty - Balázs Égert; Kirsten Lommatzsch (Bank of Finland, Institute for Economies in Transition (BOFIT), 2004)
This paper sets out to estimate equilibrium real exchange rates for the Czech Republic, Hungary, Po-land, Slovakia and Slovenia.A theoretical model is developed that provides an explanation for the ap-preciation of the real exchange rate based on tradable prices in the acceding countries.Our model can be considered as a competing but also completing framework to the traditional Balassa-Samuelson model.With this as a background, alternative cointegration methods are applied to time series (Engle-Granger, DOLS, ARDL and Johansen) and to three small-size panels (pooled and fixed effect OLS, DOLS, PMGE and MGE), which leaves us with around 5,000 estimated regressions.This enables us to examine the uncertainty surrounding estimates of equilibrium real exchange rates and the size of the underlying real misalignments.
URN:NBN:fi:bof-201408072021
Keywords: F31; 330; Real exchange rate; equilibrium exchange rate; tradable prices; transition; cointegration